Running dynamics in shuttle run between competitive and recreational athletes of intermittent sports - Muhammad Zaki Ghazali Abdullah Tan (Nanyang Technological University, 2021)
The sprint-stop-turn-sprint movement in the shuttle run is a key movement in most intermittent sports. It is executed countless of times during practice and competition which gives rise to the concern of overuse injuries. Studies have examined the acute injuries related to this movement but there is a lack of emphasis on the overuse injury aspect. The first aim of this study was to investigate the relationship between step length and the ground reaction force (GRF) while decelerating. The second aim was to compare the performance between competitive and recreational intermittent sports players. For this study, peak force and force gradient were the variables that represent GRF. 58 male participants were recruited for the study (mean ± SD, age 23.8 ± 1.2 years, body mass 71.2 ± 11.2 kg). They were tasked to complete 3 laps of shuttle run with sufficient rest in between. Pearson’s Correlation test indicated that there was no significant relationship between both step length and peak force (r = 0.039, p = 0.780), and between step length and force gradient (r = -0.222, p = 0.103). MANOVA analysis showed that there were no significant difference between competitive and recreational players for step length, peak force and force gradient [F(3, 51) = 1.713, p = 0.176, TracePillai = 0.092] despite a better performance by the competitive group. From this study, step length did not affect the GRF during the deceleration phase of the shuttle run and that there was no significant difference between competitive and recreational players.